The rat nervous system - Paxinos, George, 1944- (Elsevier/Academic Press, 2015)
The previous editions of The Rat Nervous System were indispensable guides for those working on the rat and mouse as experimental models. The fourth edition enhances this tradition, providing the latest information in the very active field of research on the brain, spinal cord, and peripheral nervous system. The structure, connections, and function are explained in exquisite detail, making this an essential book for any graduate student or scientist working on the rat or mouse nervous system.Completely revised and updated content throughout, with entirely new chapters add.